Rapid thermal annealing induced formation of Ge nanoparticles in ZnO thin films: A detailed SAXS study. (June 2015) - Ceylan, Abdullah; Tatar Yildirim, Leyla; Ozcan, Sadan; Ismat Shah, S.
Abstract: In this study, germanium nanoparticles (Ge-np) embedded ZnO multilayered thin films were produced on z-cut quartz and Si substrates by sequential r.f. sputtering of ZnO and d.c. sputtering of Ge targets followed by an ex-situ rapid thermal annealing (RTA) process performed at 600 °C for 30, 60, and 90 s. Evolution of Ge-np via an RTA process has been investigated in detail especially by using a small angle x-ray scattering (SAXS) technique. X-ray diffraction (XRD) patterns showed that fcc diamond phase Ge-np were successfully formed in c -axis oriented ZnO host. Crystallite sizes of diamond phase Ge-np calculated by the Scherrer formula were in the range of 18–27 nm. Analysis of SAXS patterns revealed that optimum RTA time at 600 °C to form monodispersed Ge-np is 60 s. Moreover, 30 s RTA was inadequate for the complete crystallization and segregation of crystalline Ge-np; 90 s RTA turned out to be improving the crystallite size as well as deteriorating the isolation of Ge-np possibly by inter diffusion of Ge atoms back to ZnO host. These results suggest that RTA applied under certain conditions is a robust and scalable route to form monodispersed well crystallized Ge-np in ZnO multilayered thin films for various applications.